Study guides

☆☆

Q: How do you Factorise 4ab - 6ab?

Write your answer...

Submit

Still have questions?

Continue Learning about Algebra

2a(2b-c) :P

It is: 3a(2b -3c) when factored

The greatest common factor of 4ab and 6ab is 2ab. You simply take the greatest common factor from both factors. The greatest common factor of 4 and 6 is 2. The letters can be factored out because they appear in both factors

2a*2b = 4ab

5a2 + 6ab=a(5a+6b)

Related questions

2a(2b) Would Give You The Answer 4ab. 2x2 = 4 And a x b = ab.

It is: 2a(2b+c)

2a(2b-c) :P

It is: 3a(2b -3c) when factored

4ab - 2a - 7

The greatest common factor of 4ab and 6ab is 2ab. You simply take the greatest common factor from both factors. The greatest common factor of 4 and 6 is 2. The letters can be factored out because they appear in both factors

Assuming that non-leading numbers are exponents, the expression becomes12a^2b + 8a - 5a^2b + 2ab - 4ab^2 + 6ab - 2a - 3ab= 7a^2b + 6a + 5ab - 4ab^2= a*(7ab + 6 + 5b - 4b^2)

2a x 3b = 6ab

4ab

5a³ - 4ab + 2a³ = (5+2)a³ - 4ab = 7a³ - 4ab.

2a*2b = 4ab

3a2b is the simplest formImproved Answer:-3a x 2b = 6ab when simplified

People also asked